An inverse problem in estimating fracture toughness of TiAlN thin films by finite element method based on nanoindentation morphology. (October 2021) - Jiang, Z.T.; Li, Y.G.; Lei, M.K.
Abstract: The fracture toughness of TiAlN thin films on AISI 304 austenitic stainless steel was inversely investigated by combining nanoindentation experiment with finite element method (FEM) and extended FEM (XFEM) simulation. The TiAlN thin films were deposited by deep oscillation magnetron sputtering (DOMS) with the oscillation pulse on and off times of 12 μs and 30 μs at a peak power of 136.1 kW. A completely dense TiAlN thin film with the thickness of 1500 nm has a face-centered-cubic microstructure with (200) preferred orientation. The displacements of the nanoindenter were intentionally interrupted by 1200 nm and 1800 nm, latter is thin film-crossing to induce an apparently cracking. The cross-sectional samples of TiAlN thin films with the cracks were fabricated by focused ion beam. The experimental crack number and position in the cross-sectional samples were observed by scanning electron microscopy. The maximum damage initiating stress (σmax ) and corresponding crack separation distance (δc ) in the Griffith–Irwin relationships were fitted using the XFEM calculation based on the crack morphology to match the crack number and position of TiAlN thin films. The fracture toughness of TiAlN thin films on AISI 304 austenitic stainless steel was calculated to be 1.09 MPa m 1/2 according to the fitted parameters of 5.5 GPa for σmax and 1.5 nm for δc . Therefore, an alternative method by the nanoindentation morphology and the inversely calculation fitting was developed to estimate the fracture toughness of thin films. Highlights: 1. TiAlN thin films were deposited on steel by deep oscillation magnetron sputtering. 2. Fracture toughness was evaluated by extended finite element method and experiments. 3. Key fracture parameters of TiAlN thin films were solved as an inverse problem. 4. Crack separation distance and maximum damage initiating stress were key parameters. 5. Experimental and calculated similarity in crack number and position was established.